Methods for autonomously decomposing and performing long-horizon sequential decision tasks - Pateria, Shubham (Nanyang Technological University, 2022)
Sequential decision-making over long timescales and in complex task environments is an important problem in Artificial Intelligence (AI). An effective approach to tackle this problem is to autonomously decompose a long-horizon task into a sequence of simpler subtasks or subgoals. We refer to this approach as Autonomous Task Decomposition (ATD) in the thesis and study it for multi-agent coordination using model-free Hierarchical Reinforcement Learning (HRL), single-agent goal-reaching using model-free HRL, and single-agent goal-reaching using model-based planning. The objective of the thesis is to develop novel methods to address three important challenges related to ATD, which are as follows: 1. Effective multi-agent HRL under sparse global rewards and complex inter-dependencies among agents. 2. Efficient unification of autonomous subgoal discovery and single-agent HRL without slow learning. 3. Learning models for planning-based ATD that produce more rewarding and feasible plans. In this regard, the thesis introduces three novel ATD methods as follows: 1. Inter Subtask Empowerment based Multi-agent Options (ISEMO) is introduced for effective multi-agent HRL by using auxiliary rewards that capture the inter-dependencies among HRL agents and their (handcrafted) subtasks. ISEMO leads to better coordinated performance of the inter-dependent agents on a complex Search & Rescue task, compared to a standard multi-agent HRL method. 2. End-to-End Hierarchical Reinforcement Learning with Integrated Discovery of Salient Subgoals (LIDOSS) is introduced for efficient unification of subgoal discovery and HRL for single-agent goal-reaching, by using a probability-based subgoal discovery heuristic integrated with the subgoal selection policy. LIDOSS accelerates end-to-end learning and leads to higher goal-reaching success rates compared to a state-of-the-art HRL method. 3. Finally, Learning Subgoal Graph using Value-based Subgoal Discovery and Automatic Pruning (LSGVP) is introduced to learn subgoal graph-based planning models that produce more rewarding and feasible plans for single-agent goal-reaching. LSGVP uses cumulative reward-based subgoal discovery and automatic pruning of erroneous connections in the subgoal graph. It achieves higher positive cumulative rewards and higher success rates compared to other state-of-the-art subgoal graph-based planning methods, while also being more data-efficient than model-free HRL.